A study of the service load of public secondary school teachers in the City of Manila - Penaranda, Rosario Beringuel 1933- (University of the Philippines], 1954)
This study determines the total service load of public high school teachers in the City of Manila, the types of activities related to teaching that the teacher performs, and the time left for professional and cultural growth and health and recreational activities.